Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
6-2(x-y)=-3x+5
6-2x+2y=-3x+5
6-2x+2x+2y=-3x+2x+5
6+2y=-x+5
6-6+2y=-x+5-6
2y=-x-1
2y+x=-x+x-1
x+2y=-1
Therefore, the standard form of 6-2(x-y)=-3x+5 is x+2y=-1.
Answer: The correct option is
(A) [tex]x+2y=-1.[/tex]
Step-by-step explanation: We are given to select the option that shows the following equation in standard form :
[tex]6-2(x-y)=-3x+5~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
We know that
the standard form of the equation of a line is ax + by = c.
From equation (i), we get
[tex]6-2(x-y)=-3x+5\\\\\Rightarrow 6-2x+2y=-3x+5\\\\\Rightarrow 6-2x+2y+3x=5\\\\\Rightarrow x+2y=5-6\\\\\Rightarrow x+2y=-1.[/tex]
Thus, the required standard form of the equation of line is [tex]x+2y=-1.[/tex]
Option (A) is CORRECT.
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.